Joshua, King David, and the Flying Nun: Doodles and Reader Annotations in Post-Holocaust Yiddish Primers for Children - Borden, Miriam (Canadian Jewish Studies / Études juives canadiennes, 2024)
Students in Yiddish supplementary schools used texts produced by educators steeped in a diaspora nationalist pedagogy that reflected the ideological coupling of Yiddish and Yiddishkeit: the Yiddish language informed one’s sense of Jewishness. By the 1960s, doodles students left in their schoolbooks challenged this coupling of language and identity. Though it is generally supposed that Yiddish primers ultimately tell us more about the aspirations of adults than they do about the experiences of children, reading these texts together reveals that children evolved their own relationship between Yiddish and Jewishness that was far more subtle than what they encountered in their textbooks. Postwar primers emphasize maintaining the Yiddish language on American soil, to the exclusion of the external culture; children’s doodles argue that more important than preserving the language was locating Yiddishkeit in the culture around them.